(untitled) (Research, Society and Development, 2023)
The intestinal microbiota is a natural environment with species of different bacteria, including pathogenic ones. The incorrect use of antibiotics causes the number of opportunistic bacteria to be greater, causing low immunity. In the vast majority of cases, antibiotics are sold without a medical prescription, causing the number of cases of bacterial resistance to increase. Therefore, the main objective of the article is to investigate the effects of antibiotic consumption on the intestinal microbiota and how such impacts can be reversed. For this work, an integrative bibliographic review study was carried out, using the keywords "microbiota, antibiotics, immunity, intestine and probiotics", the main search tools were PubMed, Google Scholar and SciElo. In the analysis, 5 main articles were selected in order to explain the risks and consequences of this relatively common habit. The results explain the physiological concepts that motivated the research and the relevant data. With the use of probiotics correctly prescribed by a healthcare professional, there is the possibility of mitigating the side effects of the pertinent use of antibiotics on the intestinal flora.